Exploring Trends And Dimensions In Islamic Leadership Research: A Bibliometric Approach - Syaifullah, syaifullah; Lestari, Nurrizka Puji; Juirah, Juirah; Damirah, Damirah (ITB AAS INDONESIA Surakarta, 2024)
This research aims to examine the trends and the extent of research related to Islamic Leadership in Indonesia published through the Scopus database from 2013 to 2023. The research method employed is quantitative, applying bibliometric analysis and utilizing R-Packages and WebInterface Biblioshiny software for visual data analysis and detailing. The study indicates that the theme of Islamic Leadership in Indonesia continues to capture the attention of researchers to the present day. One of the most influential works is Sholikhah's publication in 2019, cited 32 times. Diponegoro University has the highest affiliation with 13 publications, and Indonesia stands out as the most productive country with a total of 319 citations. The bibliometric analysis conducted is limited to Scopus data, with other national and international databases not considered in this study. This research examines relevant studies on Islamic leadership in Indonesia, presenting a brief literature review accessible to researchers in this field and providing recommendations for future research.